Impact of Lockdown due to COVID-19 on lifestyle and diet pattern of college students of Eastern India: A cross-sectional survey (Nepal Journal of Epidemiology, 2022)
Background: The emergence of the COVID-19 pandemic and lockdown measures to confine it has disrupted the routine of the public. The impact of such long-term confinements on the lifestyle and diet of students are not known and hence this study was designed to assess the impact of lockdown due to the COVID-19 pandemic on the lifestyle and  diet of university students.Methods: An online cross-sectional survey among 622 university students across various educational institutes of east India using a pre-designed questionnaire about lifestyle-diet before and during the lockdown. Results were tabulated and statistical tests like Paired t-test, Wilcoxon Rank sign test, and Mc-Nemar tests were applied and overall significance was attributed to P